2007
DOI: 10.1055/s-2007-966556
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of persistent bacteremia after endoscopic injection of N-butyl-2-cyanoacrylate for gastric varices bleeding

Abstract: − late has been used successfully for the he− mostatic treatment of bleeding gastric varices [1]. Various complications asso− ciated with the procedure have been re− ported [2]. The prevalence of infectious complications could range from 4.3 % to 50 %, and most are transient and unevent− ful [3]. Because prolonged and persistent septic complications have been rarely re− ported, the appropriate strategy of man−

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…This paper reports that FDG PET/CT clearly showed an abnormal hypermetabolic lesion around the N-butyl-2-cyanoacrylate plug with improvement after treatment with antibiotics and finally diagnosing the site of infection. Liao SC et al reported on a case in which gallium-67 scan was used in identification of the infection site [7] and Wahl P et al reported on a case in which gastroscopy along with abdomen CT postulated the source of infection [8]. In a study on FUO patients who underwent both FDG PET and Ga scintigrahy, Blockmans et al [9] found that FDG PET showed more abnormalities than Ga scintigraphy (77% vs 67% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This paper reports that FDG PET/CT clearly showed an abnormal hypermetabolic lesion around the N-butyl-2-cyanoacrylate plug with improvement after treatment with antibiotics and finally diagnosing the site of infection. Liao SC et al reported on a case in which gallium-67 scan was used in identification of the infection site [7] and Wahl P et al reported on a case in which gastroscopy along with abdomen CT postulated the source of infection [8]. In a study on FUO patients who underwent both FDG PET and Ga scintigrahy, Blockmans et al [9] found that FDG PET showed more abnormalities than Ga scintigraphy (77% vs 67% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of this complication is unknown but remains probably low. Only few cases have been described in literature [2, 4]. Bacteremia is generally transient without clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…As probably reported in the first case and in the literature, the communication between the gastrointestinal lumen and the vascular spaces leads to recurrent bacteremia [2, 4]. Another well-known complication is a glue embolization [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…75 A few reports have described recurrent bacteremia from an infected glue conglomerate in the GV this has been successfully treated with repeated courses of antibiotics. 76,77 A recent report described GVO complicated by pyogenic spleno-portal thrombosis which led to persistent Klebsiella pneumoniae septicemia. The glue plug is a foreign body that offers an ideal surface for bacterial colonization and becomes a reservoir for continuous bacterial dissemination.…”
Section: Journal Of Clinical and Experimental Hepatologymentioning
confidence: 99%